Inhibitory Effect of Anoectochilus formosanus Extract on Hyperglycemia-Related PD-L1 Expression and Cancer Proliferation - Ho, Yih; Chen, Yan-Fang; Wang, Li-Hsuan; Hsu, Kuang-Yang; Chin, Yu-Tang; Yang, Yu-Chen S. H.; Wang, Shwu-Huey; Chen, Yi-Ru; Shih, Ya-Jung; Liu, Leroy F.; Wang, Kuan; Whang-Peng, Jacqueline; et al. (Frontiers in Pharmacology, 2018)
Traditional herb medicine, golden thread (Anoectochilus formosanus Hayata) has been used to treat various diseases. Hyperglycemia induces generation of reactive oxygen species (ROS) and enhancement of oxidative stress which are risk factors for cancer progression and metastasis. In this study, we evaluated hypoglycemic effect of A. formosanus extracts (AFE) in an inducible hyperglycemia animal model and its capacity of free-radical scavenging to establish hyperglycemia-related carcinogenesis. AFE reduced blood glucose in hyperglycemic mice while there was no change in control group. The incremental area under blood glucose response curve (AUC)s was decreased significantly in hyperglycemic mice treated with AFE in a dose-dependent manner. AFE and metformin at the same administrated dose of 50 mg/kg showed the similar effect on intraperitoneal glucose tolerance test (IGTT) in hyperglycemic mice. Free-radical scavenger capacity of AFE was concentration dependent and 200 μg/ml of AFE was able to reduce more than 41% of the free radical. Treatment of cancer cells with AFE inhibited constitutive PD-L1 expression and its protein accumulation. It also induced expression of pro-apoptotic genes but inhibited proliferative and metastatic genes. In addition, it induced anti-proliferation in cancer cells. The results suggested that AFE not only reduced blood glucose concentration as metformin but also showed its potential use in cancer immune chemoprevention/therapy via hypoglycemic effect, ROS scavenging and PD-L1 suppression.